Barriers and Facilitators to Implementing a Digital Adherence Technology for Tuberculosis Treatment Supervision in Uganda: Qualitative Study - Anna Leddy; Joseph Ggita; Christopher A Berger; Alex Kityamuwesi; Agnes Nakate Sanyu; Lynn Kunihira Tinka; Rebecca Crowder; Stavia Turyahabwe; Achilles Katamba; Adithya Cattamanchi (JMIR Publications, 2023)
BackgroundEnsuring the completion of treatment for tuberculosis (TB) remains a key challenge in many high-burden countries. 99DOTS is a low-cost digital adherence technology that has emerged as a promising tool for monitoring and supporting TB treatment completion. ObjectiveWe aimed to understand the feasibility and acceptability of 99DOTS, a mobile phone-based TB treatment support method, and characterize barriers and facilitators to its implementation during a pragmatic trial in Uganda. MethodsBetween April 1 and August 31, 2021, we conducted in-depth interviews with people with TB and key informant interviews with health workers and district and regional TB officers involved in the implementation of 99DOTS at 18 health facilities in Uganda. Semistructured interview guides were informed by the capability, opportunity, motivation, and behavior (COM-B) model and explored perceptions of, and experiences with, 99DOTS, including barriers and facilitators to its use. Qualitative analysis was conducted using the framework approach. ResultsInterviews were conducted with 30 people with TB, 12 health workers, and 7 TB officers. All people with TB, health workers, and TB officers noted that 99DOTS supported and encouraged people with TB to take their anti-TB medication, facilitated treatment monitoring, and improved relationships between people with TB and health workers. Participants also liked that the platform was free, easy to use, and improved TB treatment outcomes. Barriers to 99DOTS implementation for some people with TB were related to limited literacy, including technology literacy; limited access to electricity to charge their mobile phone to make dosing confirmation calls; and poor network connection. Gender differences in 99DOTS uptake also emerged. Specifically, women with TB were described to be more concerned that 99DOTS use would expose them to TB stigma and to be more likely to have mobile phone-access issues than men with TB. By contrast, men with TB not only had access to mobile phones but also received substantial support from their female partners to take their anti-TB medication and make 99DOTS dosing confirmation calls. Finally, although women with TB were described to face more barriers to 99DOTS use than men with TB, the women's narratives centered on the ways the platform facilitated and improved their adherence, whereas the men's narratives did not. ConclusionsOverall, 99DOTS seems to be a feasible and acceptable strategy to support anti-TB medication adherence in Uganda. However, access to mobile phones, inability to charge mobile phones, and concerns about stigma should be considered and addressed as part of programmatic implementation to maximize uptake among all people with TB, particularly women and those with fewer financial resources.